The walnut tree as a source of progesterone for reproductive control in goats - P. Chemineau; A.L. Lainé; D. Gennetay; C. Porte; D. Chesneau; C. Laclie; G. Goudet; M. Meunier; M. Delmas; M.L. Greil; P. Liere; A. Pianos; et al. (Animal)
Intravaginal sponges impregnated with the progesterone (P4) analogue fluorogestone acetate (FGA) induce synchronous oestrous behaviour and normal ovulatory cycle in goats. To explore alternatives using natural P4 from plants, we developed a method of ethanolic extraction and a specific enzyme immunoassay (EIA) to measure P4 in the different parts of the walnut tree Juglans regia. We found a very high concentration of P4, specifically in the leaves of the three most common French varieties (∼100 mg/kg of DM) but not in flowers, fruits, septa, husk, oil or cake. High concentrations of P4—and to a lesser extent its reduction metabolites and phytosterols—were also measured by Gas Chromatography-Mass Spectrometry/Mass Spectrometry in leaf extracts. P4 concentrations were five times higher in October than in June. P4 was detected in 182 varieties of Juglans regia ranging from 35 to 287 mg of P4 per kg of leaf DM. We collected large quantities of leaves over 6 years, which were used to manufacture feed pellets containing 32% of dry leaf for distribution to female goats. To determine their dietary acceptance and their efficacy in terms of P4 blood plasma concentration, three trials in ovariectomised goats and four trials in ovary-intact goats were performed (N = 83). The distribution of 600 g of pellets per day per ovary-intact goat over 3 days, 6 and 4 days before the introduction of males in April allowed us to achieve our objective of a significant increase of P4 plasma concentration to ∼1.5 ng/mL measured by EIA from 24 to 72 h after the first distribution in the walnut pellet group (n = 13). The two control groups of goats (FGA, n = 12 and control, n = 10) showed no increase in plasma P4. However, despite this high P4 plasma concentration, goats of the walnut group had the same percentages of goats in oestrus at the first ovulation and of goats experiencing short ovulatory cycles after introduction of males (54 and 77%, respectively) as the group of control goats (80 and 90%), whereas the FGA goats showed very different percentages (100 and 0%, P < 0.01). It was concluded that whereas walnut leaves contain a high concentration of P4—and its reduction metabolites and phytosterols—the pellet feeding mode does not allow for restoration of oestrus behaviour and duration of the induced cycle consistently achieved with FGA-impregnated intravaginal sponges.